Hearing Preservation in Vestibular Schwannoma Surgery - Saliba, Joe (J Neurol Surg B Skull Base, 2019)
Modern imaging techniques allow early detection of small vestibular schwannomas (VSs) with minimal or no hearing impairment. While controversy surrounds the management of these tumors, given their benign nature and unpredictable natural history, microsurgical excision is the only modality that offers the opportunity to cure the tumor and preserve hearing. Hearing preservation in VS surgery may be accomplished via the middle fossa or retrosigmoid approaches. Appropriate patient selection and surgical approach is critical in achieving the best hearing outcomes. This article highlights the preoperative assessment, patient selection and prognostic factors, intraoperative monitoring of hearing, and surgical approaches to optimize hearing preservation during VS removal.